Influence of OCT2 gene variants on metformin efficacy in type 2 diabetes: insights into pharmacogenomics and drug interactions - Ma’mon M. Hatmal; Omar Abuyaman; Mohammad A. I. Al-Hatamleh; Heba Tayyem; Amin N. Olaimat; Ali Mussa; Iman Aolymat; Aymen Abuawad; Mohanad Odeh; Rana Qawaqzeh (Journal of Translational Medicine)
Abstract Metformin, a widely prescribed treatment for type 2 diabetes mellitus (T2DM), demonstrates significant inter-individual variability in its therapeutic response. This variability is potentially driven by genetic differences in drug transporters. Among these transporters, the organic cation transporter 2 (OCT2) plays a critical role in the pharmacokinetics of metformin by mediating its uptake into renal epithelial cells for excretion. This review explores the potential impact of genetic variations in OCT2 gene (SLC22A2) on the pharmacokinetics and pharmacodynamics of metformin. These genetic variations can alter metformin accumulation in the kidneys, impacting its overall clearance and therapeutic effectiveness. Furthermore, the interactions of metformin with other drugs, especially in T2DM patients, can compromise its pharmacokinetics. Thus, it is important to consider the influence of genetic variability and potential drug interactions when prescribing metformin. Incorporating genetic testing into clinical decision-making could help optimize dosing strategies and improve treatment outcomes, particularly when managing patients with complex comorbid conditions.